2, 4, 6-Tribromophenol Disposition and Kinetics in Rodents: Effects of Dose, Route, Sex, and Species. (15th February 2019) - Knudsen, Gabriel A; Trexler, Andrew W; Richards, Alicia C; Hall, Samantha M; Hughes, Michael F; Birnbaum, Linda S
Abstract: 2, 4, 6-tribromophenol (TBP, CAS No. 118-79-6) is widely used as a brominated flame retardant and wood antifungal agent. TBP is frequently detected in environmental matrices, biota, and humans. In female SD rats, systemically available TBP (10 µmol/kg, IV) was rapidly excreted primarily via urine, with approximately 61% of the dose recovered after 4 h, and 89%–94% in 24 h; 5% was recovered in feces; and 1%–2% in blood/tissues. TBP administered to female SD rats (0.1–1000 µmol/kg) by gavage was well absorbed, with approximately 25% eliminated via urine after 4 h and approximately 88% after 24 h. Approximately 11% of a single oral dose was recovered in bile. Male SD rats and B6C3F1/J mice of both sexes had similar disposition profiles when administered a single oral dose of TBP (10 µmol/kg). Following administration, fecal recoveries varied only slightly by dose, sex, or species. TBP readily passed unchanged through both human ( ex vivo only) and rat skin with between 55% and 85% of a 100 nmol/cm 2 passing into or through skin. Concentrations of TBP in blood fit a two-compartment model after IV-dosing and a one-compartment model after oral dosing. Urine contained a mixture of TBP, TBP-glucuronide, and TBP-sulfate. Fecal extracts contained only parent TBP whereas bile contained only TBP-glucuronide. TBP did not appear to bioaccumulate or alter its own metabolism after repeated administration. TBP was readily absorbed at all doses and routes tested with an oral bioavailability of 23%–27%; 49% of TBP is expected to be dermally bioavailable in humans. From these data, we conclude that humans are likely to have significant systemic exposure when TBP is ingested or dermal exposure occurs.